ANALISIS PERSEPSI KINESTETIK DAN MOTIVASI TERHADAP KEMAMPUAN MEMANAH ATLET SULSEL PADA CABANG OLAHRAGA PANAHAN - Akbar, Andi Khemal (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2017)
The research aimed at examining (1) whether there is contribution of kinesthetic perception to archery abilityof South Sulawesi athletes in archery sport, (2) whether there is contribution of motivation to archery abilityof South Sulawesi athletes in archery sport, (3) whether there are contribution of kinesthetic perception motivation to archery abilityof South Sulawesi athletes in archery sport. This study employed quantitative approach with descriptive correlational type. Data were collected through kinsthetic perception test, motivation questionnire, and archery abylity tests. Data analysis techniques used were descriptive statistics test, inferensial statistics tests, end statistics tests to test the hypothesis by using simple regression analysis and multiple regression analysis. The results of the research reveal that: (1) there is contribution of kinesthetic perception to archery ability of South Sulawesi athletes by 36.9% and 63.1% is caused by another factors that is not explained in this research, (2) there is contribution of motivation to archery ability of South Sulawesi athletes by 42.7% and 57.3% is caused by another factors that is not explained in this research, (3) there is contibutions of both kinesthetic perception and motivation to archery ability of South Sulawesi athletes by 53.1 and 46.9 is caused by another factors that is not explained in this research.